Cross-regulation of viral kinases with cyclin A secures shutoff of host DNA synthesis - Boris Bogdanow (Nature Portfolio, 2020)
Herpesviruses code for conserved protein kinases (CHPKs) that exert several regulatory functions by interacting with cellular factors. Here, the authors use affinity purification mass spectrometry (AP–MS) to identify differential interaction partners of CHPKs from seven different human herpesviruses, finding Cyclin A and associated factors as a specific signature of β-herpesvirus kinases.